Temperature‐Driven Dengue Transmission in a Changing Climate: Patterns, Trends, and Future Projections - Fengliu Feng; Yuxia Ma; Pengpeng Qin; Yuhan Zhao; Zongrui Liu; Wanci Wang; Bowen Cheng (GeoHealth)
Abstract Dengue is a rapidly spreading mosquito‐borne infectious disease that is sensitive to climate factors and poses a major public health concern worldwide. We analyzed dengue incidence trends and the relationship between annual mean minimum temperatures (AMMTs) and dengue incidence rates from 1990 to 2019 in 122 countries using the Global Burden of Disease and TerraClimate data sets. We also projected global dengue incidence rates under different carbon emission scenarios using temperature data from the Coupled Model Intercomparison Project Phase 6 (CMIP6) data set. Our results reveal a significant increase in global dengue cases from 1990 to 2019 and a positive correlation between temperature and dengue incidence. The association between AMMT and dengue incidence strengthened at temperatures exceeding 21°C. Central and eastern sub‐Saharan Africa, as well as Oceania, were identified as the regions most sensitive to dengue; males and individuals aged 15–19 or 70–84 years were the most susceptible to dengue under rising temperatures. Our projections suggest that global dengue incidence will substantially increase by 2050 and 2100. By 2100, regions including Africa, the Arabian Peninsula, the southern United States, southern China, and island countries in the Pacific and Indian Oceans are projected to become year‐round dengue‐endemic under a high‐emission climate scenario. Our findings underscore the importance of implementing effective measures to mitigate the impact of climate change on dengue transmission. Identifying high‐risk areas and susceptible populations, along with understanding the projected expansion of dengue‐endemic regions, will provide valuable guidance for targeted interventions to address this growing global health challenge in the face of changing climatic conditions.